Elimination of Congo Red Dyes From Aqueous Solution Using Eichhornia Crassipes - Ali, Hamza Qassim; Mohammed, Ahmed A (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
Water hyacinth (Eichhornia crassipes) is a free-floating plant, growing plentifully in the tropical water bodies. It is being speculated that the large biomass can be used in wastewater treatment, heavy steel and dye remediation, as a substrate for bioethanol and biogas production, electrical energy generation, industrial uses, human food and antioxidants, medicines, feed, agriculture, and sustainable improvement. In this work, the adsorption of Congo Red (CR) from aqueous solution onto EC biomass was investigated through a series of batch experiments. The effects of operating parameters such as pH (3-9), dosage (0.1-0.9 g. /100 ml), agitated velocity (100-300), size particle (88-353μm), temperature (10-50˚C), initial dye concentration (50-500) mg/l, and sorption–desorption were investigated to assess the efficiency of EC-elimination from aqueous solution. Different pre-treatments, alkali, and acid were achieved to increase the adsorption uptake. The optimum conditions for maximum removal of CR from an aqueous solution of 50 mg/L were as follows: pH (6), particle size (88 μm), stirring speed (200 rpm), and dose (0.3 g). The experimental isotherms data were analyzed using Langmuir, Freundlich, and Temkin isotherm equations and the results indicated that the Langmuir isotherm showed a better fit for CR adsorption with a higher adsorption uptake of 92.263mg/g, and the kinetic data were fitted well with pseudo-second-order kinetic model. Thermodynamic parameters were calculated from Van’t Hoff plot, confirming that the adsorption process was spontaneous and endothermic. Data show that the adsorption-desorption process lasts for four cycles before losing its efficiency and the recovery efficiency increased up to 76.63%.